Novel resin-based filtering material as well as preparation method and application thereof

By loading CTF/CuS composite photocatalyst on the cation exchange resin, the problem of the reduction of adsorption capacity and difficulty in regeneration of traditional resins in the treatment of complex wastewater is solved, and efficient adsorption and photocatalytic degradation of aminoglycoside antibiotics in antibiotic wastewater is achieved.

CN119912024AActive Publication Date: 2025-05-02赣州亿茂环境科技有限公司
View PDF 14 Cites 0 Cited by

Patent Information

Application Number
CN202510412668.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-03
Publication Date
2025-05-02
Estimated Expiration
2045-04-03

AI Technical Summary

Technical Problem

Traditional ion exchange resins are difficult to meet the needs of complex wastewater environments in water treatment, especially in removing aminoglycoside antibiotics in difficult-to-degrade antibiotics, which have problems such as decreasing adsorption capacity and difficulty in regeneration.

Method used

The CTF/CuS composite photocatalyst material is supported on the cation exchange resin support to form a core-shell structure, and antibiotics are electrostatically adsorbed by the sulfonic acid group of the strongly acidic cation exchange resin, and photocatalytic degradation is performed through the heterojunction photocatalyst of CTF/CuS.

Benefits of technology

It has achieved efficient adsorption and photocatalytic degradation of aminoglycoside antibiotics in antibiotic wastewater, with high adsorption and high catalytic degradation properties, and can continuously and effectively treat antibiotic wastewater and maintain high adsorption-degradation properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_9
    Figure SMS_9
Patent Text Reader

Abstract

The invention relates to the technical field of filter materials, in particular to a novel resin-based filter material and a preparation method and application thereof.The resin-based filter material takes cation exchange resin as a matrix and is loaded with a CTF / CuS composite photocatalyst; wherein the CTF accounts for 8.71-12.04% of the total mass of the filtering material, and the nano CuS accounts for 4.16-7.68% of the total mass of the filtering material; the resin-based filtering material is applied to antibiotic wastewater treatment. The novel resin-based filtering material prepared by the invention can efficiently remove aminoglycoside antibiotics in a water body, is high in cycling stability, and can still reach a kanamycin removal rate of 97.5% or above when being used for the second time.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of filter materials, and in particular to a novel resin-based filter material and a preparation method and application thereof. Background Art

[0002] Ion exchange resin is an insoluble polymer compound with an active group for exchanging ions and a network structure. Its full name is ion exchange polymer compound. It is usually used in water treatment, food industry (such as sugar, monosodium glutamate, wine, etc.), pharmaceutical industry, synthetic chemistry and petrochemical industry, and air purification (such as removing acidic gas, alkaline gas, VOC, butane, etc.). Ion exchange resins can be divided into gel type and macroporous type according to their pore structure. The macroporous resin has a physical pore structure. It can also be divided into styrene resin and acrylic resin according to the type of its matrix, and further divided into cationic resin and anionic resin. Among them, cationic resin is divided into strong acid and weak acid, anionic resin is divided into strong alkaline and weak alkaline, or medium-strong acid and medium-strong alkaline.

[0003] The working principle of ion exchange resin is to exchange ions in the solution through its chemically active groups, so as to achieve the purpose of removing or separating ions. For example, strong base anion exchange resin contains strong basic groups, which can adsorb and combine with anions in the solution to produce anion exchange; after a period of use, the resin usually needs to be regenerated with strong alkali (such as NaOH) and other chemical agents to restore its exchange capacity.

[0004] Since ion exchange resins have excellent adsorption properties, they are easily contaminated by organic matter and colloids in water bodies, resulting in a decrease in exchange capacity and difficulty in regeneration; at the same time, traditional ion exchange resins usually only use a single ion exchange effect to adsorb and remove impurities and pollutants in wastewater, which is difficult to meet the needs of complex water treatment. In order to solve the above problems, various functional ion exchange resin-based composite materials have emerged in an endless stream, and have become one of the research hotspots in the field of filtration materials. For example, the invention patent with application number CN201710003826.7 discloses a nuclear-grade ion exchange resin-based composite material and a preparation method thereof, which is a loaded catalyst obtained by assembling a platinum precursor, a silicon source, an aluminum source and a nuclear-grade ion exchange resin. The carrier is a nuclear-grade ion exchange resin, and the active load is a core-shell structure composite, the core is nano-platinum particles, and the shell is a platinum-silicon-aluminum molecular sieve composite with a porous silicon-aluminum molecular sieve. The synergistic effect of the three is beneficial to simultaneously exert the ion exchange effect of the ion exchange resin and the element exchange effect of the precious metal platinum nanocatalyst, thereby improving the removal and purification efficiency and recycling regeneration capacity; the composite material is 24 Na + The decontamination efficiency can reach 92.7%, and the decontamination rate of the composite material is greater than 88.9% after 10 cycles of use.129 I - The decontamination efficiency reaches 96.7%, and the decontamination rate of the composite material is greater than 91.8% after 10 cycles. For example, the invention patent with application number CN202010664155.0 discloses an ion exchange resin-based composite material and its preparation method. Ce-MOF is first prepared by reacting nitrogen-containing heterocyclic aromatic carboxylic acid compounds and cerium sources. After carbonization, a carbon-nitrogen material-cerium oxide composite is obtained, and then a strong acid styrene-based ion exchange resin is used for adsorption and loading to prepare an ion exchange resin-based composite material. The directional enrichment effect of porous carbon-nitrogen materials is used to achieve the adsorption of organic pollutants. At the same time, cerium oxide is used as a photocatalyst, and its oxygen-rich vacancy characteristics can achieve the degradation of low-content organic matter, thereby achieving effective removal of organic pollutants. For example, the invention patent with application number CN202211106636.5 discloses a particle-enhanced ion exchange resin and its preparation method and application, including a carrier resin, an inorganic ion exchanger and a particle enhancer, wherein the inorganic ion exchanger and the particle enhancer are coated in the carrier resin; the carrier resin is calcium alginate; the inorganic ion exchanger includes one or two of ammonium phosphotungstate and ammonium phosphomolybdate; the particle enhancer includes at least one of silicon-containing inorganic micro-nano particles and titanium-containing inorganic micro-nano particles, and when the ion exchanger is pure ammonium phosphotungstate, it has good selective adsorption of cesium in a 0.1~5mol / L nitric acid system, the adsorption rate can reach more than 97%, and the distribution coefficient is higher than 1000cm 3 / g, which can be used for cesium in high-level radioactive waste liquid in strong nitric acid system and for filling ion exchange columns to separate cesium in high-level radioactive waste liquid. For example, the invention patent with application number CN202311216126.8 discloses an anion resin-based nano cerium-manganese oxide composite material, preparation method and application, including anion exchange resin, the anion exchange resin matrix is ​​polystyrene-divinylbenzene or polyacrylic acid, the functional group is a quaternary ammonium group or a tertiary amine group, and the matrix pores are loaded with nano hydrated cerium oxide particles and nano hydrated manganese oxide particles. The mass fraction of cerium in the composite material is 7-16%, and the mass fraction of manganese is 6-15%. In the process of removing As(III), Mn(IV) oxide nanoparticles first oxidize As(III) to As(V) which is less toxic and easier to be adsorbed, and then Ce(IV) oxide nanoparticles adsorb As(V), realizing the simultaneous oxidation-adsorption removal of As(III), and the anion exchange groups on the resin can realize the pre-enrichment and enhanced diffusion of target pollutants through the Donnan membrane effect. For example, the invention patent with application number CN202310367802.5 discloses a preparation method and application of a resin-based magnetic composite adsorption material. Waste ion exchange resin is used as the raw material, and after airflow expansion and pore expansion, it is magnetically modified, and then sodium phosphite and sodium hypophosphite are added. After microwave heating reaction, the composite adsorption material is obtained. When the pH value of the solution is 4, the removal rate of cadmium, chromium, copper, zinc, and nickel by the adsorption material is more than 90%, and the removal rate of manganese is also 87.01%, which has good performance in removing heavy metal ions. For example, the invention patent with application number CN202411282013.2 discloses an in-situ ecological restoration agent for river and lake sediments and its preparation process. PEG is fixed to the surface of carboxylated nitrile rubber modified SBS elastomer particles through an esterification reaction, and then crown ether, ethylenediaminetetraacetic acid and dimercaptosuccinic acid are subjected to an esterification reaction with the hydroxyl groups carried by PEG to obtain carboxylated nitrile rubber modified SBS elastomer composite ester particles. On the one hand, the adsorption capacity for heavy metals can be improved, and on the other hand, the introduction of harmful substances can be reduced; by cooperating with montmorillonite particles, heavy metal ions in aqueous solution can be quickly removed, thereby improving the restoration effect on river and lake sediments; by adding anion and cation exchange resins and column chromatography silica gel, nitrogen and phosphorus compounds and other harmful ion groups in river and lake sediments can be adsorbed to improve the restoration effect; by adding coconut shell granular activated carbon, on the one hand, the restoration effect on organic pollutants and heavy metals can be improved, and on the other hand, it can also deodorize.

[0005] In order to further develop functional resin-based filter materials to meet the water treatment needs of complex wastewater environments, the present invention loads CTF / CuS composite photocatalyst materials on a cation exchange resin carrier for the first time and applies them to antibiotic wastewater treatment, especially for the degradation treatment of wastewater containing aminoglycoside antibiotics. Summary of the invention

[0006] In view of this, the purpose of the present invention is to propose a new type of resin-based filter material and its preparation method and application. On the one hand, a functional resin-based filter material that can be photocatalytically degraded is developed to meet the water treatment needs of complex wastewater environments. On the other hand, a new idea is provided for the treatment of antibiotic wastewater.

[0007] Based on the above purpose, the present invention provides a new resin-based filter material, which uses a cation exchange resin as a matrix and loads a CTF / CuS composite photocatalyst; wherein CTF accounts for 8.71-12.04% of the total mass of the filter material, and nano-CuS accounts for 4.16-7.68% of the total mass of the filter material.

[0008] Furthermore, the cation exchange resin is a strongly acidic cation exchange resin.

[0009] Furthermore, the strongly acidic cation exchange resin is selected from one or more of D001, D072, Amberlite IRP69, Amberlite 200, and Lewatit Sp-210 cation exchange resins.

[0010] The present invention further provides a method for preparing a novel resin-based filter material, comprising the following steps: S1: Add terephthalonitrile to trifluoromethanesulfonic acid, stir for 10-15 minutes, then add cation exchange resin, stir and react at 25-30°C for 18-24 hours, then heat to 70-85°C, stir and react for 3-6 hours, filter, wash and dry to obtain CTF loaded cation exchange resin; S2: Add alkali metal sulfide salt into deionized water, stir to dissolve, add CTF loaded cation exchange resin, stir for 10-15 minutes, then add soluble divalent copper salt, stir and react at 30-40°C for 12-18 hours, filter, wash and dry to obtain a new resin-based filter material.

[0011] Furthermore, the alkali metal sulfide salt is selected from one or more of sodium sulfide, potassium sulfide and lithium sulfide.

[0012] Furthermore, the soluble divalent copper salt is selected from one or more of copper nitrate, copper sulfate and copper acetate.

[0013] Furthermore, the usage ratio of the terephthalonitrile, trifluoromethanesulfonic acid, cation exchange resin, alkali metal sulfide salt, deionized water, and soluble divalent copper salt is (0.1-0.15) g:1 mL:1 g:(0.5-1) mmol:2 mL:(0.5-1) mmol.

[0014] The present invention further provides application of the novel resin-based filter material prepared by the preparation method in the treatment of antibiotic wastewater.

[0015] Furthermore, the antibiotic wastewater is wastewater containing aminoglycoside antibiotics.

[0016] Furthermore, the aminoglycoside antibiotic-containing wastewater is antibiotic wastewater containing one or more of kanamycin, gentamicin, tobramycin, ethimicin, and amikacin.

[0017] Beneficial effects of the present invention: The present invention loads a CTF / CuS composite photocatalyst material on a cation exchange resin carrier for the first time, presenting a core-shell structure, and is applied to antibiotic wastewater treatment, and is particularly suitable for the degradation treatment of difficult-to-degrade wastewater containing aminoglycoside antibiotics. The aminoglycoside antibiotics are electrostatically adsorbed by the sulfonic acid groups rich in the surface of the strong acid cation exchange resin, and the antibiotic pollutants are quickly enriched on the resin matrix. The CTF / CuS heterojunction photocatalyst loaded on the matrix is ​​then used to photocatalytically degrade the antibiotic molecules. The three synergistically enhance the efficiency, have high adsorption performance and high catalytic degradation performance, and realize the dynamic cycle treatment of "adsorption-photocatalytic degradation-re-adsorption-re-photocatalytic degradation..." of organic pollutants. Even in the absence of regeneration, the antibiotic wastewater can be continuously and effectively treated, and the high adsorption-degradation performance can be maintained.

[0018] Compared with a single cation exchange resin, the new resin-based filter material has better adsorption and degradation performance. The reason for this is that, on the one hand, the photocatalyst on the new resin-based filter material catalyzes the degradation of organic pollutants and is always in a dynamic unsaturated adsorption state under light conditions, making it difficult for the cation exchange resin to reach saturation equilibrium; on the other hand, the loaded CTF has a high specific surface area, which helps to improve the adsorption capacity of the filter material to a certain extent.

[0019] Compared with resin-based filter materials loaded with single CTF or single nano-CuS, the resin-based filter material uses cation exchange resin as a carrier, loads CTF, and further in-situ chemically deposits nano-CuS. Different from resin-based filter materials loaded with a single pure phase catalyst, the inventors construct a heterojunction catalyst on the cation exchange resin to drive the photogenerated electrons to jump from the valence band of nano-CuS to the conduction band of CTF, so that the photogenerated holes are retained in the valence band of nano-CuS, effectively improving the electron-hole separation efficiency and avoiding the agglomeration of nano-CuS particles. At the same time, the composite of CTF and nano-CuS expands the spectral response range, covering the entire visible light to near-infrared band, improving the utilization rate of sunlight, and thereby improving the light conversion efficiency and catalytic performance, and enhancing the catalytic degradation performance of antibiotics.

[0020] At the same time, under the premise of a certain amount of photocatalyst, compared with the CTF / CuS composite photocatalyst, the new resin-based filter material breaks through the efficiency bottleneck of a single photocatalytic material through the triple synergistic enhancement of "adsorption → enrichment → degradation", and shows better catalytic degradation performance. The reason for this may be that, on the one hand, the cation exchange resin carrier itself can physically remove aminoglycoside antibiotics through electrostatic adsorption; on the other hand, the cation exchange resin is used to transform the catalyst component from "passive catalysis" to "active adsorption-catalysis". The composite phase CTF / CuS is used as a photocatalyst, relying on the free diffusion of pollutants in the solution to contact the active sites. However, due to the low concentration of aminoglycoside antibiotics in wastewater, the photocatalytic reaction is limited by the mass transfer efficiency and the degradation rate is low. The present invention increases the "local concentration of antibiotic molecules in the region" through the pre-enrichment effect of the sulfonic acid groups in the resin matrix on aminoglycoside antibiotics, thereby significantly improving the contact efficiency between the loaded CTF / CuS heterojunction photocatalyst and the antibiotics, shortening the h + The distance that the holes migrate to the antibiotic contaminants can reduce the energy loss of the holes during the transmission process; at the same time, in the acidic microenvironment of the cation exchange resin, the aminoglycoside antibiotics Protonated , which reduces the electron cloud density of its glycosidic bond and amino side chain, making it easier to be or OH attack, which in turn causes Directly oxidize the amino group to allow ·OH to attack and break the glycosidic bond, thereby improving the efficiency of selective and directional degradation of aminoglycoside antibiotics.

[0021] The novel resin-based filter material prepared by the present invention can efficiently remove aminoglycoside antibiotics in water and has high circulation stability. When used for the second time, the removal rate of kanamycin can still be as high as more than 97.5%. DETAILED DESCRIPTION

[0022] In order to make the objectives, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with specific embodiments.

[0023] The present invention provides a novel resin-based filter material according to an embodiment. The resin-based filter material is based on a cation exchange resin and loaded with a CTF / CuS composite photocatalyst; wherein CTF accounts for 8.71-12.04% of the total mass of the filter material, and nano CuS accounts for 4.16-7.68% of the total mass of the filter material; In this embodiment, the cation exchange resin is a strongly acidic cation exchange resin; In this embodiment, the strongly acidic cation exchange resin is preferably one or more selected from D001, D072, Amberlite IRP69, Amberlite 200, and Lewatit Sp-210 cation exchange resins.

[0024] This embodiment is the first to load a CTF / CuS composite photocatalyst material on a cation exchange resin carrier, presenting a core-shell structure, and is applied to antibiotic wastewater treatment, and is particularly suitable for the degradation treatment of difficult-to-degrade wastewater containing aminoglycoside antibiotics. The aminoglycoside antibiotics are electrostatically adsorbed by the sulfonic acid groups rich in the surface of the strong acid cation exchange resin, and the antibiotic pollutants are quickly enriched on the resin matrix. The CTF / CuS heterojunction photocatalyst loaded on the matrix is ​​then used to photocatalytically degrade the antibiotic molecules. The three synergistically enhance the efficiency, have high adsorption performance and high catalytic degradation performance, and realize the dynamic cycle treatment of "adsorption-photocatalytic degradation-re-adsorption-re-photocatalytic degradation..." of organic pollutants. Even in the absence of regeneration, the antibiotic wastewater can be continuously and effectively treated to maintain high adsorption-degradation performance.

[0025] Compared with a single cation exchange resin, the new resin-based filter material has better adsorption and degradation performance. The reason for this is that, on the one hand, the photocatalyst on the new resin-based filter material catalyzes the degradation of organic pollutants and is always in a dynamic unsaturated adsorption state under light conditions, making it difficult for the cation exchange resin to reach saturation equilibrium; on the other hand, the loaded CTF has a high specific surface area, which helps to improve the adsorption capacity of the filter material to a certain extent.

[0026] Compared with resin-based filter materials loaded with single CTF or single nano-CuS, the resin-based filter material uses cation exchange resin as a carrier, loads CTF, and further in-situ chemically deposits nano-CuS. Different from resin-based filter materials loaded with a single pure phase catalyst, the inventors construct a heterojunction catalyst on the cation exchange resin to drive the photogenerated electrons to jump from the valence band of nano-CuS to the conduction band of CTF, so that the photogenerated holes are retained in the valence band of nano-CuS, effectively improving the electron-hole separation efficiency and avoiding the agglomeration of nano-CuS particles. At the same time, the composite of CTF and nano-CuS expands the spectral response range, covering the entire visible light to near-infrared band, improving the utilization rate of sunlight, and thereby improving the light conversion efficiency and catalytic performance, and enhancing the catalytic degradation performance of antibiotics.

[0027] At the same time, the inventors also found that under the premise of a certain amount of photocatalyst, compared with the CTF / CuS composite photocatalyst, the new resin-based filter material breaks through the efficiency bottleneck of a single photocatalytic material through the triple synergistic effect of "adsorption → enrichment → degradation", and shows better catalytic degradation performance. The reason for this may be that, on the one hand, the cation exchange resin carrier itself can physically remove aminoglycoside antibiotics through electrostatic adsorption; on the other hand, the cation exchange resin is used to transform the catalyst component from "passive catalysis" to "active adsorption-catalysis". The composite phase CTF / CuS is used as a photocatalyst, relying on the free diffusion of pollutants in the solution to contact the active sites. However, due to the low concentration of aminoglycoside antibiotics in wastewater, the photocatalytic reaction is limited by the mass transfer efficiency and the degradation rate is low. The present invention improves the "local concentration of antibiotic molecules in the region" through the pre-enrichment effect of the sulfonic acid groups in the resin matrix on aminoglycoside antibiotics, thereby significantly improving the contact efficiency between the loaded CTF / CuS heterojunction photocatalyst and the antibiotics, shortening the h + The distance that the holes migrate to the antibiotic contaminants can reduce the energy loss of the holes during the transmission process; at the same time, in the acidic microenvironment of the cation exchange resin, the aminoglycoside antibiotics Protonated , which reduces the electron cloud density of its glycosidic bond and amino side chain, making it easier to be or OH attack, which in turn causes Directly oxidize the amino group to allow ·OH to attack and break the glycosidic bond, thereby improving the efficiency of selective and directional degradation of aminoglycoside antibiotics.

[0028] The preparation method of the novel resin-based filter material of this embodiment comprises the following steps: S1: Add terephthalonitrile to trifluoromethanesulfonic acid, stir for 10-15 minutes, then add cation exchange resin, stir and react at 25-30°C for 18-24 hours, then heat to 70-85°C, stir and react for 3-6 hours, filter, wash and dry to obtain CTF loaded cation exchange resin; S2: Add alkali metal sulfide salt into deionized water, stir to dissolve, add CTF loaded cation exchange resin, stir for 10-15 minutes, then add soluble divalent copper salt, stir and react at 30-40°C for 12-18 hours, filter, wash and dry to obtain a new resin-based filter material.

[0029] In this embodiment, the alkali metal sulfide salt is preferably one or more selected from sodium sulfide, potassium sulfide, and lithium sulfide.

[0030] In this embodiment, the soluble divalent copper salt is preferably one or more selected from copper nitrate, copper sulfate, and copper acetate.

[0031] In this embodiment, the usage ratio of terephthalonitrile, trifluoromethanesulfonic acid, cation exchange resin, alkali metal sulfide salt, deionized water, and soluble divalent copper salt is (0.1-0.15) g:1 mL:1 g:(0.5-1) mmol:2 mL:(0.5-1) mmol.

[0032] In this embodiment, the novel resin-based filter material of this example is applied to antibiotic wastewater treatment.

[0033] In this embodiment, the antibiotic wastewater is preferably wastewater containing aminoglycoside antibiotics.

[0034] In this embodiment, the aminoglycoside antibiotic-containing wastewater is preferably antibiotic wastewater containing one or more of kanamycin, gentamicin, tobramycin, ethimicin, and amikacin.

[0035] Example 1 A method for preparing a novel resin-based filter material comprises the following steps: S1: Add 1 g of terephthalonitrile to 10 mL of trifluoromethanesulfonic acid, stir for 10 min, then add 10 g of D001 cation exchange resin, stir at 25 ° C for 18 h, then heat to 80 ° C, stir and react for 3-6 h, filter, wash and dry to obtain CTF loaded cation exchange resin; S2: Add 0.3902 g of sodium sulfide to 20 mL of deionized water, stir to dissolve, add the CTF-loaded cation exchange resin prepared in S1, stir for 10 min, then add 0.7981 g of copper sulfate, stir and react at 30°C for 12 h, filter, wash and dry to obtain a new resin-based filter material.

[0036] Example 2 A method for preparing a novel resin-based filter material comprises the following steps: S1: Add 1.5 g of terephthalonitrile to 10 mL of trifluoromethanesulfonic acid, stir for 15 min, then add 10 g of D001 cation exchange resin, stir at 30 ° C for 24 h, then heat to 85 ° C, stir and react for 6 h, filter, wash and dry to obtain CTF loaded cation exchange resin; S2: Add 0.7804 g of sodium sulfide to 20 mL of deionized water, stir to dissolve, add the CTF-loaded cation exchange resin prepared in S1, stir for 15 min, then add 1.5961 g of copper sulfate, stir and react at 40°C for 18 h, filter, wash and dry to obtain a new resin-based filter material.

[0037] Comparative Example 1 uses D001 cation exchange resin as the filter material.

[0038] Comparative Example 2 uses CTF-loaded cation exchange resin as the filter material.

[0039] Comparative Example 3 uses nano-CuS-loaded cation exchange resin as a filter material, and its preparation method is as follows: 0.3902 g of sodium sulfide is added to 20 mL of deionized water, and after stirring to dissolve, D001 cation exchange resin is added, and stirred for 10 min, and then 0.7981 g of copper sulfate is added, and the reaction is stirred at 30° C. for 12 h, and then filtered, washed, and dried to obtain nano-CuS-loaded cation exchange resin.

[0040] Comparative Example 4 uses CTF / CuS composite photocatalyst as a treatment material, and its preparation method comprises the following steps: S1: Add 1 g of terephthalonitrile to 10 mL of trifluoromethanesulfonic acid, stir for 10 min, react at 25 °C with stirring for 18 h, then heat to 80 °C, stir and react for 3-6 h, filter, wash and dry to obtain CTF; S2: Add 0.3902 g of sodium sulfide to 20 mL of deionized water, stir to dissolve, add CTF prepared in S1, stir for 10 min, then add 0.7981 g of copper sulfate, stir and react at 30°C for 12 h, filter, wash and dry to obtain a CTF / CuS composite photocatalyst.

[0041] The treatment performance and cyclic stability of the products prepared in the examples and comparative examples for wastewater containing aminoglycoside antibiotics were measured: Weigh 100 mg of the filter materials prepared in Examples 1-2 and Comparative Examples 1-3, and 12.9 mg of the composite photocatalyst prepared in Comparative Example 4 (consistent with the total content of the photocatalyst in the filter material in Example 1, in which CTF and nano-CuS account for 8.71% and 4.16% of the total mass of the filter material, respectively); then add them to six groups of 300 mL of 50 mg / L kanamycin aqueous solution in the dark, stir for 30 minutes, turn on a 300 W xenon lamp, stir for 60 minutes, and then measure the initial removal rate of kanamycin.

[0042] Filter and dry again, collect the test samples of Examples 1-3 and Comparative Examples 1-4, add them into six new 300 mL 50 mg / L kanamycin aqueous solution in dark conditions, repeat the above experimental process, and evaluate the cyclic stability by measuring the kanamycin removal rate of the samples during the second use.

[0043] The test results are shown in Table 1:

[0044] According to Table 1, the novel resin-based filter material prepared by the present invention can efficiently remove kanamycin in water, and has high cyclic stability. When used for the second time, its kanamycin removal rate can still be as high as 97.5% or more. However, when used for the second time, the comparative example 1 using D001 cation exchange resin as the filter material has a greatly reduced kanamycin removal rate. The reason may be that the comparative example 1 reaches a saturated adsorption amount during the second use without regeneration treatment, while the photocatalyst on the novel resin-based filter material prepared in Example 1 catalyzes the degradation of kanamycin under light conditions, so that it is always in a dynamic unsaturated adsorption state. At the same time, the loaded CTF has a high specific surface area, which helps to improve the adsorption capacity of the filter material to a certain extent.

[0045] Comparing Example 1 and Comparative Examples 2-3, it can be seen that compared with the resin-based filter material loaded with a single pure phase catalyst, Example 1 improves the removal performance of the filter material for antibiotic wastewater by loading the CTF / CuS composite catalyst on the cation exchange resin carrier. The reason for the analysis is that the present invention constructs a heterojunction catalyst on the cation exchange resin, drives the photogenerated electrons to transition from the valence band of nano-CuS to the conduction band of CTF, and retains the photogenerated holes in the valence band of nano-CuS, effectively improving the electron-hole separation efficiency, and also avoiding the agglomeration of nano-CuS particles. At the same time, the composite of CTF and nano-CuS expands the spectral response range, covering the entire visible light to near-infrared band, improving the utilization rate of sunlight, and thus improving the light conversion efficiency and catalytic performance, and improving the catalytic degradation performance of antibiotics.

[0046] By comparing Example 1 and Comparative Example 4, it can be seen that Example 1 significantly improves the treatment performance of the filter material for kanamycin wastewater by loading the CTF / CuS composite photocatalyst on the D001 cation exchange resin carrier through the triple synergistic enhancement of "adsorption → enrichment → degradation".

[0047] Those skilled in the art should understand that the discussion of any of the above embodiments is merely illustrative and is not intended to imply that the scope of the present invention (including the claims) is limited to these examples. Under the concept of the present invention, the technical features in the above embodiments or different embodiments may be combined, the steps may be implemented in any order, and there are many other variations of the different aspects of the present invention as described above, which are not provided in detail for the sake of simplicity.

[0048] The present invention is intended to cover all such substitutions, modifications and variations that fall within the broad scope of the appended claims. Therefore, any omissions, modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.

Claims

1. A novel resin-based filter material, characterized in that: The resin-based filter material uses a cation exchange resin as a matrix and is loaded with a CTF / CuS composite photocatalyst; wherein CTF accounts for 8.71-12.04% of the total mass of the filter material, and nano CuS accounts for 4.16-7.68% of the total mass of the filter material.

2. A novel resin-based filter material according to claim 1, characterized in that: The cation exchange resin is a strongly acidic cation exchange resin.

3. A novel resin-based filter material according to claim 2, characterized in that: The strongly acidic cation exchange resin is selected from one or more of D001, D072, Amberlite IRP69, Amberlite 200, and Lewatit Sp-210 cation exchange resins.

4. The method for preparing a novel resin-based filter material according to claim 1, characterized in that: The following steps are involved: S1: Add terephthalonitrile to trifluoromethanesulfonic acid, stir for 10-15 minutes, then add cation exchange resin, stir and react at 25-30°C for 18-24 hours, then heat to 70-85°C, stir and react for 3-6 hours, filter, wash and dry to obtain CTF loaded cation exchange resin; S2: Add alkali metal sulfide salt into deionized water, stir to dissolve, add CTF loaded cation exchange resin, stir for 10-15 minutes, then add soluble divalent copper salt, stir and react at 30-40°C for 12-18 hours, filter, wash and dry to obtain a new resin-based filter material.

5. The method for preparing a novel resin-based filter material according to claim 4, characterized in that: The alkali metal sulfide salt is selected from one or more of sodium sulfide, potassium sulfide and lithium sulfide.

6. The method for preparing a novel resin-based filter material according to claim 4, characterized in that: The soluble divalent copper salt is selected from one or more of copper nitrate, copper sulfate and copper acetate.

7. The method for preparing a novel resin-based filter material according to claim 4, characterized in that: The dosage ratio of the terephthalonitrile, trifluoromethanesulfonic acid, cation exchange resin, alkali metal sulfide salt, deionized water, and soluble divalent copper salt is (0.1-0.15) g: 1 mL: 1 g: (0.5-1) mmol: 2 mL: (0.5-1) mmol.

8. Use of a novel resin-based filter material prepared by the preparation method according to any one of claims 4 to 7 in the treatment of antibiotic wastewater.

9. The use according to claim 8, characterized in that: The antibiotic wastewater is wastewater containing aminoglycoside antibiotics.

10. The use according to claim 9, characterized in that: The aminoglycoside antibiotic-containing wastewater is antibiotic wastewater containing one or more of kanamycin, gentamicin, tobramycin, ethimicin and amikacin.

Citation Information

Patent Citations

  • A nuclear-grade ion exchange resin-based composite material and its preparation method

    CN106824272B

  • Ion exchange resin-based composite material and preparation method thereof

    CN111760592A

  • A particle-reinforced ion exchange resin, its preparation method and application

    CN115193489B

  • Preparation method and application of resin-based magnetic composite adsorption material

    CN116272908B

  • Anion resin-based nano-cerium-manganese oxide composite material and its preparation method and application

    CN117181202B